Investigating the comorbidity of COPD and tuberculosis, a computational study - Sershen, Cheryl L.; Salim, Taha; May, Elebeoba E. (Frontiers in Systems Biology, 2023)
Recent research has shown that people who suffer from chronic obstructive pulmonary disease (COPD) have a greater propensity to contract and develop tuberculosis (TB) than the general population. Inghammer et al. (2010) showed via regression analysis that not only is the hazard ratio for contracting active TB triple that of the general population for those with COPD, but that the probability of death from any cause during the first year was double that of the TB population as a whole, suggesting that patients with COPD are less likely to progress to latent tuberculosis infection (LTBI) and are more likely to develop active TB than the general population. While similar susceptibility rates to TB are known to occur in populations with other ailments of the lung, particularly HIV, emphysema or asthma, however patients with COPD (both emphysema and chronic bronchitis) are statistically more at risk for the disease. To examine the comorbidity effects of COPD on TB disease and granuloma formation, the process by which Mycobacterium tuberculosis (Mtb) is either contained or disseminates, we used a multi-scale model that integrates the pathophysiological and immunopathological aspects of COPD and TB. Depicting COPD smoker and non-smoker populations, we integrate agent-based models (ABM) of cellular immune response, physiological models of pulmonary capacity for COPD smoker/non-smoker, systems biology models of macrophage immune response to Mtb, and metabolic models to capture intracellular and extracellular Mtb metabolism and proliferation. We use our model to investigate key physiological and immunological drivers of disease outcomes of clearance, granuloma-based containment, and disseminated disease in individuals with COPD and TB for smoking and non-smoking populations.